Comparisonal Analysis Of Financial Distress On Sharia Bank And Conventional Bank Based On The Altman Z-Score Method - S, Muhlisa; Muhammadun, Muzdalifah; Sahara, Ira (Islamic Financial And Accounting Review, 2022)
The role of banking in advancing the economy of a country is very large. The current economy cannot be separated from the banking world. In condition that , banking sued for capable facing and overcoming financial distress. This study aim for compare the level of financial distress of Islamic banks and conventional banks with Altman Z-Score method for the period 2015-2019. This research is a quantitative study. As for the variables compared _ are net working capital to total assets (X1), retained earnings to total assets (X2), earnings before interest and taxes to total assets (X3), book value of equity to total (X4), and Z-Score. Sample chosen use method purposive sampling . As for the sample consist from Islamic banks (Bank Muamalat Indonesia, Bank BNI Syariah, and Bank Mega Syariah) and conventional banks (Bank Mandiri , Bank BRI, and Bank BTN) for the 2015-2019 period. Hypothesis testing method use Mann Whitney U Test. Test results show comparison level performance Islamic bank finance and conventional bank based on net working capital to total assets (X1) shows value 0.000 <0.05 means H0 is rejected, retained earnings to total assets (X2) shows value 0.000 <0.05 means H0 is rejected, earning before interest and taxes to total assets (X3) shows a value of 0.003 <0.05 means that H0 is rejected and the book value of equity to total liabilities (X4) shows that value 0.000 <0.05 means H0 is rejected so that there is difference significant . Whereas results comparison the level of financial distress based on the Z-Score shows value 0.178> 0.05 so that H0 is accepted . This means that no there is significant difference Among Islamic banks and conventional banks .